DEVELOPMENT OF AN EDUCATIONAL MATHEMATICS GAME TO ENHANCE MOTIVATION AND ACTIVITY OF ELEMENTARY SCHOOL STUDENTS - Bangkit Pribadi Basuki; Waris Waris; Fauzan Adhim (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to develop an educational game as a mathematics learning medium in elementary schools to enhance students' motivation and learning engagement. Many pupils struggle to grasp fundamental mathematical concepts due to low enthusiasm and limited engagement in the learning process, which renders lessons tedious. To address this issue, the research designs an interactive game based on Wordwall, enriched with a narrative flow created in Canva so that the appearance and mechanics are more appealing than a Wordwall quiz alone. The methodology rests on a qualitative approach and descriptive quantitative analysis, namely the qualitative component explores teachers' and students' needs and experiences through in‑depth interviews and classroom observations, while the descriptive quantitative component measures changes in students' motivation and activity by comparing questionnaire scores before and after the game's implementation. The research method follows the five stage ADDIE model, encompassing analysis to identify factors underlying low motivation and activity, design to draft a game concept aligned with elementary students' characteristics, development to produce a prototype using Wordwall and Canva, implementation to conduct field trials in an elementary school, and evaluation to assess the game's effectiveness in boosting motivation and engagement. The expected output is an educational game that can be applied effectively as a mathematics teaching tool, thereby improving student learning outcomes. Moreover, the study involves participation of teachers and students as primary respondents who provide input at each development stage, ensuring that the final product genuinely reflects the needs and characteristics of the elementary school learning environment.